HARMONY IN MYTH: EXPLORING THE RICH TAPESTRY OF FLORA AND FAUNA IN INDIAN MYTHOLOGY - Prabhavathy, S. (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Indian fiction has long been a canvas reflecting the rich tapestry of the country’s cultural and natural diversity. One captivating aspect that frequently finds its way into the narrative is the portrayal of flora and fauna. The integration of nature in storytelling not only adds depth to the narrative but also serves as a poignant metaphor for various facets of human life. Flora, with its myriad hues and forms, becomes a metaphor for diversity in Indian fiction. Fauna, on the other hand, introduces a different dimension to the narrative. Animals, whether symbolic or real, are often employed to convey profound messages. Regional variations in flora and fauna contribute to the diverse narrative landscape. The portrayal of flora and fauna in Indian fiction is not limited to naturalistic descriptions. Moreover, the spiritual significance of certain plants and animals is often explored in Indian fiction. The sacredness of the banyan tree or the symbolism of the lotus are seamlessly woven into narratives, reflecting the cultural and religious ethos of the characters. This incorporation of flora and fauna adds layers of meaning, creating a literary landscape that resonates with readers on a deeper level. The representation of flora and fauna is not without its challenges. Striking a balance between preserving the authenticity of the natural world and using it as a literary device requires finesse. Authors tread a fine line between romanticizing nature and addressing the pressing environmental issues that the country faces. Nevertheless, this dual role of nature in Indian fiction contributes to the genre’s richness and relevance.